Response of Cattleya hybrids for Fusarium oxysporum f. sp. Cattleyae foster - Pedroso-de-Moraes, Cristiano [UNESP]; Claro de Souza, Marcelo [UNESP]; Ronconi, Cínthia Cristina; Marteline, Marco Aurélio (My University, 2011)
The Cattleya genus has a great importance in the flower agro-business market. Fusarium wilts, caused by Fusarium oxysporum f. sp. cattleyae, is considered one of the main factors of decline and death of plants of this genus. Using seven hybrids (intra and intergenerics) of Cattleya, tests of resistance and susceptibility to F. oxysporum were performed in conditions of greenhouse for 12 months, using, as evaluation criterion, a scale of the disease severity ranging from one (resistant) to eight (highly susceptible). High susceptibility to the fungus by Cattleya Nobile's Wax Toy, Cattleya Orquidacea's Mister Fast intrageneric hybrids and Potinara Orquidacea's Havana Brown intergeneric hybrid, related to Brassocattleya Orquidacea's Melody intergeneric hybrid, high resistance to the pathogens was observed.
Keywords: Fusarium wilts; Orchid; Varietal resistance